Political trust of the Dayak Paser indigenous law community regarding the capital city relocation policy - Tengku Imam Syarifuddin; Dian Eka Rahmawati; Dafid Efendi (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The country’s capital will succeed if it works well as the national government center, a prosperous and livable city. As the country’s multifunctional capital, Jakarta has undoubtedly caused many social, political, and economic problems that are difficult to overcome. This article aims to determine the political trust in the indigenous law community of Dayak Paser concerning the national capital relocation policy, using qualitative analysis consisting of a literature study approach with Nvivo 12 Plus application to analyze the data derived from internet websites. The author used government alignments, cultural norms, and economic change as the indicators in this study. The author also separates the community of Dayak Paser into the indigenous law community and the indigenous leaders. The result is that the members of the indigenous law communities prefer the sustainability of the cultural norms. The dominant indigenous figures prefer the government’s alignments. If the government guarantees the standard order, then the indigenous law community’s site and rights will not go extinct. Indigenous leaders and the members of the indigenous law community are equally subordinate to the economic factors. The conclusion that the government’s alignment toward sustainability cultural norms affects the economic changes. The author also recommends that the country’s capital design should use a metaphorical concept approach.